Influence of Service Quality, Water Tariffs, and Technological Innovation on PDAM Tirtanadi Customer Satisfaction - Pane, Aulia Ramadani; Nasution, Yenni Samri Juliati; Nurwani (Yayasan Sinergi Kawula Muda, 2024)
It is known that the increasing water bill arrears at PDAM Tirtanadi HM Yamin Branch are due to customers' lack of satisfaction with the quality of service, water rates and technological innovation offered. Finding connections and evaluating the impact of the three independent variables on the dependent variable—customer satisfaction—is the goal of this study. The technological innovation variable is novel and has never been investigated in tandem with other variables. This study employs a quantitative associative approach methodology. The sample was determined using the Slovin formula so that there were 100 respondents, with a research population of 27,904 people. The following test were employed in the study of this research: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test, f test, and coefficient of determination test. The findings of the study indicate that: (1) service quality to customer satisfaction are positively and significantly correlated; (2) water tariffs to customer satisfaction are positively and significantly correlated; (3) technological innovation to customer satisfaction are positively and significantly correlated; and (4) service quality, water rates, and technological innovation are positively and significantly correlated to customer satisfaction at the same time. PDAM Tirtanadi HM Yamin branch needs to improve service quality, suitability of water tariffs, and socialize the use of technological innovations that have been launched.